Estudo teórico sobre membranas peptídicas e lipídicas: uma análise via dinâmica molecular - Alves, Eyber Domingos (2021)
In this work, the molecular dynamics formalism was used to study the physicochemical properties of peptide and lipid membranes when immersed in solution. Concerningpeptide membranes, the energetic and structural properties were evaluated in the situations in which these membranes were immersed in the Ionic Liquid (IL) formed by the choline (COL) and glycine (GLY) pair. The results indicate the existence of energetic and structural stability of these membranes when in IL, with potential application in energy storage in biodegradable supercapacitors. For lipid membranes, we used the umbrella sampling technique to proceed with a series of 150 insertions of the Fullerene-C 60 molecule in four lipid membranes composed of DOPC (Dipalmitoylphosphatidylcholine) at a ratio of 00% (pure membrane), 10%, 20% and 30% of cholesterol molecules, evaluating the average behavior of molecular insertion energies. The results showed that the presence of cholesterol molecules makes the inclusion process of Fullerene-C 60 energetically unfavorable. Under the computational pathway, we evaluated the pharmacological characteristics associated with monomers constructed based on peptides. For this purpose, we interact the lipid membranes composed of DOPC (Dipalmitoylphosphatidylcholine) at a proportion of 00% (pure membrane), 10% and 30% of cholesterol molecules with the peptide drug L-GL13K. The results reveal that the hydrogen bonds between the compound L-GL13K and the DOPC molecules promote membrane destabilization and increasing the infiltration of water molecules.